The metal/organic interface in cobalt/vinylidene fluoride heterostructures. (3rd November 2016) - Foreman, K; Echeverria, E; Koten, M A; Lindsay, R M; Hong, N; Shield, J; Adenwalla, S
Abstract: Organic-based electronic devices are rapidly increasing in popularity, making it essential to understand and characterize the interface between organic materials and metallic electrodes. This work reports on the characterization of the interface between thin films of an emerging organic ferroelectric, vinylidene fluoride (VDF) oligomer, and Co, an important high Curie temperature ferromagnet. Using a wide battery of experimental techniques, it is shown that VDF oligomer thin films as thin as 15 nm can halt, or prevent, Co oxidization in atmospheric conditions, a necessary condition for device applications. Selectivity of magnetic properties, such as remanent magnetization, is enabled by the clarification of the time scale of Co oxidation, a topic on which there are many conflicting reports. Furthermore, this work shows evidence of chemical bonding at the interface between VDF oligomer and Co, a result with important implications for organic spintronic devices. These results establish the suitability of VDF oligomer for organic-based electronic devices.